Decellularized matrix could affect the proliferation and differentiation of periodontal ligament stem cells in vitro. (26th June 2021) - Huang, Jia‐Ping; Wu, Yan‐Min; Liu, Jia‐Mei; Zhang, Lan; Li, Bo‐Xiu; Chen, Li‐Li; Ding, Pei‐Hui; Tan, Jing‐Yi
Abstract: Objective and Background: Recently, decellularized matrix (DCM) is considered as a new biomaterial for tissue regeneration. To explore the possible application of DCM in periodontal regeneration, the effect of DCM from three different cells on the proliferation and differentiation of human periodontal ligament stem cells (PDLSCs) was investigated. Methods: DCM derived from human periodontal ligament cells (PDLCs), dental pulp cells (DPCs), and gingival fibroblasts (GFs) were fabricated using Triton X‐100/NH4 OH combined with DNase I. Allogeneic PDLSCs were cultured on PDLC‐DCM, DPC‐DCM, and GF‐DCM, respectively. The proliferative capacity of PDLSCs was evaluated by PicoGreen assay kit. The expression of alkaline phosphatase (ALP), runt‐related transcription factor‐2 (RUNX2), osteocalcin (OCN), collagen I (COL1), periostin (POSTN), and cementum protein 1 (CEMP1) were detected by qRT‐PCR and western blotting. Results: PDLC‐DCM, DPC‐DCM, and GF‐DCM had similar and integrated networks of extracellular matrix, as well as significantly decreased DNA content. Compared with control group in which PDLSCs were directly seeded in culture plates, PDLC‐DCM, DPC‐DCM, and GF‐DCM promoted the proliferation of re‐seeded PDLSCs. Additionally, PDLSCs on DCM exhibited higher mRNA and protein expression levels of ALP, RUNX2, OCN, and COL1. The expression of POSTN in PDLC‐DCM group was significantly higher than control group at both mRNA and protein levels. Conclusions: PDLC‐DCM, DPC‐DCM, and GF‐DCM could enhance the proliferation of PDLSCs. PDLC‐DCM facilitated osteogenic differentiation and periodontal ligament differentiation of PDLSCs, while DPC‐DCM and GF‐DCM promoted osteogenic differentiation.